Interpersonal Communication Between Mothers and Children in Reducing Fatherlessness in Bahagia Subdistrict, Bekasi City - Habib Nur Muhammad Taufik; Yessi Sri Utami (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2025)
This study explores the dynamics of interpersonal communication between mothers and their children in mitigating the effects of fatherlessness in Bahagia Subdistrict, Bekasi City, Indonesia. Fatherlessness—defined as the absence of a father figure in a child’s emotional and developmental life—has become an increasingly significant social phenomenon, with Indonesia ranking among the highest in the world for fatherless households. The study aims to understand how single mothers manage emotional communication and perform dual parental roles to sustain their children’s psychological well-being. Using a qualitative descriptive approach, data were collected through in-depth interviews and participant observation involving three single mothers and four children living in Bahagia Subdistrict. The findings reveal that effective interpersonal communication—grounded in openness, empathy, supportiveness, positiveness, and equality—strengthens emotional bonds, builds trust, and fosters resilience in children growing up without fathers. Moreover, such communication becomes a key coping mechanism that enables mothers to reduce the negative psychological and social consequences of fatherlessness, such as low self-esteem, social withdrawal, and academic decline. The study contributes to the field of family communication by illustrating the adaptive strategies of single mothers in Indonesia as they balance affection, discipline, and economic responsibilities. The results highlight how communication can function not only as an emotional bridge but also as a practical tool for building stability and maintaining harmony in single-parent households.